Land use and cover change in Japan and Tokyo's appetite for meat - Gadda, T; Gasparatos, A (2009)
Urban consumption of ecosystems services such as food generates environmental impacts at different geographical scales. In the last few decades Tokyoites have shown an increasing appetite for meat. This study examines the environmental implications of Tokyo's increasing meat consumption by analyzing how this trend has affected land use and cover change in areas near and far away. Historical databases (1970-2005) are employed in order to explore meat consumption patterns in Tokyo and to relate it with beef and pork production in areas within the country and abroad. It also integrates the historical analysis of production and consumption patterns with a discussion of the drivers (e.g., wealth, price, policies and seafood availability) behind these trends. We identified that meat production in Japan followed three distinct phases between 1877 and 2005. In the first period it took 50 years for production to increase by 50%, while during the next phase production showed the same growth in just half the time. Major changes in land use/ cover change because of domestic meat production occurred mainly during the second phase and, thereafter, when domestic production declined and was substituted to a great extent by imports. Despite the increasing consumption of imported meat, Tokyo relies greatly on domestic meat produced in its neighboring prefectures. The paper concludes that regional planning can be used as an effective instrument to protect the environment and secure protein for the population of mega-urban areas such as Tokyo. © Integrated Research System for Sustainability Science, United Nations University, and Springer 2009.